Editorial: Leukocyte‐targeting toxins as therapeutics in allergic asthma. Issue 3 (1st March 2015) - Sharma, Namit; Craig, Andrew W. B.
Abstract : Discussion on leukotoxin A as a potential therapeutic target to halt the recruitment of inflammatory leukocytes in allergic asthma.